Cases on database technologies and applications - Khosrowpour, Mehdi, 1951- (Hershey PA : Idea Group Pub., 2006)
"This case book presents many real-life examples and experiences of those involved in database research and database technology applications and management"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information technology -- Management -- Case studies; Database management -- Case studies